Value creation in corporate e-learning platforms - Kanervisto, Tatu (My University, 2023)
As the corporate world goes more and more digital, all functions of companies need to follow the trend. Learning and staff training is no exception. Companies are transforming the learning of employees to a digital format by using different kinds of e-learning platforms. These platforms can bring a lot of value to organizations if they are used correctly and for a clear purpose. By using e-learning platforms properly, companies can make the learning of employees more efficient and save significant amount of time and money due to savings e.g., in travelling costs. Interest towards e-learning itself has been growing amongst scholars. However, the existing literature mostly focuses on e-learning in a traditional student-teacher setting. Not many studies focus on e-learning in the context of staff training and people development in a corporate context. As companies around the world are already using e-learning platforms to develop the knowledge and knowhow of their employees, there is a research gap in corporate e-learning and how value is created in it. This study aims to fill the research gap of value creation in corporate e-learning platforms and the purpose of the study is to explore the various ways in which value is created in these corporate e-learning platforms. This research was done in collaboration with Turku School of Economics’ Centre for Collaborative Research unit to help them understand the key factors in successful corporate e-learning platforms. The empirical research of this study was conducted as expert interviews. The interviewees are HR professionals who have experience in the management and administration of e-learning platforms from the customer side. This gave the study a point of view of the customer organization. The interviews were conducted as theme interviews based on the theoretical framework of the study. The findings of the study were that there are three key factors that bring value to customer organizations in corporate e-learning platforms: training data, easy usability, and efficiency. Combining these value propositions from the service provider side with three value drivers from the customer side, commitment, planning, and communication, value can be created in collaboration between the service provider and the customer organization.

Yritysmaailman muuttuessa yhä enemmän digitaaliseksi, yritysten kaikkien toimintojen pitää pysyä muutoksessa mukana. Henkilöstön kehittäminen ei ole poikkeus. Yritykset käyttävät digitaalisia työkaluja, kuten e-oppimisalustoja, oppimisen tukena ja tehostuskeinona. Nämä alustat luovat arvoa yrityksille, jos niitä käytetään oikein selkeään tarkoitukseen. Käyttämällä e- oppimisalustoja asianmukaisesti, yritykset voivat tehostaa työntekijöidensä oppimista ja säästää huomattavasti aikaa ja rahaa esimerkiksi matkustuskustannuksista. Tutkijoiden kiinnostus e-oppimista kohtaan on ollut kasvavaa. Aikaisempi kirjallisuus on kuitenkin pääasiassa keskittynyt e-oppimiseen perinteisessä opettaja-oppilas asetelmassa. Yrityskontekstissa tapahtuvaan henkilöstön kouluttamiseen ja henkilökohtaiseen kehittymiseen ei ole kiinnitetty paljoa huomiota. Kun yritykset ympäri maailmaa käyttävät e-oppimisalustoja kehittääkseen työntekijöidensä tietoja ja taitoja, on olemassa tutkimusaukko e-oppimisesta yrityskontekstissa ja siitä, mistä arvo e-oppimisalustoilla yrityskontekstissa muodostuu. Tämä tutkimus täyttää tuota tutkimusaukkoa. Tämän tutkimuksen tarkoituksena on tutkia tapoja, joilla arvoa luodaan e-oppimisalustoilla yrityskontekstissa. Tämä pro gradu -tutkielma on tehty yhteistyössä Turun kauppakorkeakoulun Centre for Collaborative Research -yksikön kanssa tuomaan lisää ymmärrystä niistä avainasioista, jotka ovat keskeisiä onnistuneen e-oppimisalustan kehittämisessä. Tämän tutkimuksen empiirinen osio toteutettiin asiantuntijahaastatteluina. Haastateltavat ovat henkilöstöalan ammattilaisia, joilla on kokemusta e-oppimisalustan hallinnoinnista asiakasorganisaation puolella. Tämä mahdollisti asiakasorganisaation näkökulman saamisen tutkimukseen. Haastattelut toteutettiin teemahaastatteluina pohjautuen tutkimuksen teoreettiseen viitekehykseen. Tutkimuksen tulokset osoittavat, että on kolme selkeää avaintekijää, jotka tuovat arvoa asiakkaalle e-oppimisalustalla yrityskontekstissa: koulutusdata, helppokäyttöisyys ja tehokkuus. Kun nämä palveluntarjoajan puolelta tulevat arvolupaukset yhdistetään kolmeen asiakasorganisaation puolelta tulevaan arvoa luovaan tekijään, sitoutuneisuuteen, suunnitelmallisuuteen ja kommunikaatioon, arvoa voidaan luoda yhteistyössä palvelun tarjoajan ja asiakasorganisaation välillä.
Keywords: E-learning, Value creation, E-learning platform, LMS